(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2014)
Sir William Osler (1849-1920), asserted that there should be “no teaching without a patient for a text, and the best is that taught by the patient himself [1]." The objective of the medical colleges is production of good doctors. Bedside clinical teaching in the presence of patients is the most relevant to this aim. Clinical teaching is concerned with the learning of several clinical skills such as history taking, physical examination, clinical reasoning, decision making, communication, and professionalism (such as learning how to work in teams, and how to interact with the public). More than half of the patients’ problems can be diagnosed after history taking, and up to 75% of these problems can be diagnosed by the end of physical examination [2]. The traditional clinical teacher will maintain that there is no substitute for clinical bedside teaching, while the modern educationalist will opt for multimedia applications, audio CDs and patient simulators [2,3]. Although bedside teaching has been a mainstay of medical education since Osler, it has declined substantially in recent years [4-8]. JCMCTA 2013 ; 24 (2): 1-3